Magnetic Anisotropy in Coni Nanowire Arrays: Analytical Calculations and Experiments - Altbir-Drullinsky, D; Escrig-Murua, J; Allende-Prieto, S (2012)
Ordered arrays of Co xNi 1-x nanowires (0<x<1) were fabricated by a template-assisted method using electrodeposition into anodic aluminum oxide membranes. Tuning of the Co-alloy composition by changing the Ni content enables control of the effective anisotropy axis, which is determined by the balance between the hcp and fcc magnetocrystalline and shape anisotropies. We report on the nanowires structural and magnetic properties (e.g., hysteresis curves and their parameters as well as first-order reversal curve analysis), paying particular attention to their angular dependence. It is confirmed that the crystal phase of nanowires with length 2.5 ?m and diameter 35 nm shifts from hcp to fcc as the Ni content increases. That results in a significant modification of the magnetization process and, accordingly, of the magnetic properties of the array. Analytical calculations of the angular dependence of the coercivity allow us to confirm that the magnetization reversal is mostly ascribed to the propagation of a transverse domain wall. Fitting of the experiment to these calculations indicates the presence of a transverse crystalline anisotropy (ascribed to the hcp phase) in Co wires, while this changes to an axial anisotropy (fcc phase) as the Ni content increases. © 2012 American Physical Society.